ChemInform Abstract: Carboxylative Cyclization of Propargylic Amines with CO2 Catalyzed by Dendritic N‐Heterocyclic Carbene—Gold(I) Complexes. Issue 25 (June 2016) - Fujita, Ken‐ichi; Inoue, Kensuke; Sato, Junichi; Tsuchimoto, Teruhisa; Yasuda, Hiroyuki
Abstract: Amphiphilic dentritic NHC‐gold complexes are employed as catalysts for the cyclization of propargyl amines and CO2 to give oxazolidinones under mild reaction conditions.